From Symbol to Substance : A Theological and Psychological Study on the Differences in Leadership With and Without Rank Insignia - Amirrudin Zalukhu (International Forum of Researchers and Lecturers, 2025)
Leadership is often associated with symbols, one of which is the rank insignia worn by regional leaders in Indonesia. This symbol is believed to provide legitimacy and authority to leaders; however, its effectiveness remains debatable, especially when compared to regional leaders in other countries who do not wear rank insignia. This study analyzes rank insignia from the perspectives of Christian theology and leadership psychology to understand its impact on performance, competence, and public perception of leadership. From a Christian theological perspective, ideal leadership emphasizes service over symbolic authority. Meanwhile, in psychological studies, rank insignia can enhance a leader’s confidence but may also create psychological distance from the public and increase mental pressure. This study compares the effectiveness of regional leadership with and without rank insignia, considering factors such as competence, transparency, and public participation. The analysis reveals that the substance of leadership is more important than visual symbols such as rank insignia. These findings provide implications for developing leadership based on performance and inclusivity, while also encouraging further research on the psychological impact of leadership symbols in modern governance.